Applications and Prospects of Non-viral Vectors in Bone Regeneration - Yang, Wei; Wang, Fengzhe; Feng, Longbao; Yan, Shina; Guo, Rui (Current Gene Therapy, 2018)
Introduction: Bone tissue has an intrinsic ability to repair and regenerate itself through a continuous remodelling cycle of resorption of old or damaged bone and deposition of new. However, significant morbidity and mortality arise when bone cannot heal itself. Effective bone regeneration strategy can improve the current clinical therapies of many orthopaedic disorders. Cell activity stimulation, growth factors, and appropriate mechanical conditions are essential components of clinical treatment. However, growth factors tend to degrade over time in the human body. Gene therapy offers an alternative method to cure bone defects, with the advent of exciting new delivery capabilities via gene vectors. Gene vectors accurately deliver regenerative molecules to the lesion site. Additionally, gene therapy provides a highly efficient treatment option with a lower effective concentration. Compared with viral gene vectors, non-viral gene vectors have proven to be more potent due to their safety, non-immunogenicity, and ease of manufacture. Conclusion: Thus, in this paper, we review the application and progress of non-viral gene vector therapy in bone regeneration.
Keywords: Gene therapy